Nonmotor Symptoms in Subjects Without Evidence of Dopaminergic Deficits. Issue 7 (15th March 2015) - Sprenger, Fabienne S.; Seppi, Klaus; Djamshidian, Atbin; Reiter, Eva; Nocker, Michael; Mair, Katherina; Göbel, Georg; Poewe, Werner
ABSTRACT Background A subgroup of patients initially diagnosed with Parkinson's disease (PD) turn out to have normal dopamine transporter single‐photon emission computed tomography imaging and have been labeled as subjects without evidence of dopaminergic deficit (SWEDDs). In this study, we sought to further characterize these patients and have analyzed the frequency of nonmotor symptoms (NMS) in SWEDDs, PD patients, and healthy controls. Methods We analyzed the baseline clinical data of 412 PD patients, 184 controls, and 62 SWEDDs included in the Parkinson's Progression Marker Initiative study on a variety of different NMS questionnaires. Results Both PD patients and SWEDDs had greater frequency of NMS than healthy controls. Furthermore, some NMS, such as orthostatic hypotension as well as cardiovascular and thermoregulatory dysfunction were even more commonly reported in SWEDDs than in PD patients, whereas hyposmia was more common in PD, compared to SWEDDs. Conclusion NMS are more frequent in SWEDDs than in controls, and autonomic dysfunction and orthostatic hypotension were even more common than in PD patients. These findings support the notion that SWEDDS represent a group of patients with still poorly understood pathophysiology. © 2015 International Parkinson and Movement Disorder Society